Philosophy for A-level year 2 metaphysics of god and metaphysics of mind - Cardinal, Daniel; Jones, Gerald; Hayward, Jeremy (AQA A-level philosophy, 2018)
Enable students to critically engage with the new 2017 AQA specifications with this accessible Student Book that covers the key concepts and philosophical arguments, offers stimulating activities, provides a key text anthology and assessment guidance. - Cements understanding of complex philosophical concepts and encourages students to view ideas from different approaches through clear and detailed coverage of key topics. - Strengthens students' analytical skills to develop their own philosophical interpretations using a variety of inventive and thought-provoking practical activities and tasks. - Encourages students to engage with the anthology texts, with references throughout and relevant extracts provided at the back of the book for ease of teaching and studying. - Stretches students' conceptual analysis with extension material. - Helps AS and A-level students to approach their exams with confidence with assessment guidance and support tailored to the AQA requirements